2023
DOI: 10.3390/ijms24043207
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Transporters MCT8 and OATP1C1 Are Expressed in Pyramidal Neurons and Interneurons in the Adult Motor Cortex of Human and Macaque Brain

Abstract: Monocarboxylate transporter 8 (MCT8) and organic anion transporter polypeptide 1C1 (OATP1C1) are thyroid hormone (TH) transmembrane transporters that play an important role in the availability of TH for neural cells, allowing their proper development and function. It is important to define which cortical cellular subpopulations express those transporters to explain why MCT8 and OATP1C1 deficiency in humans leads to dramatic alterations in the motor system. By means of immunohistochemistry and double/multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 153 publications
5
29
0
Order By: Relevance
“…In agreement with the previous findings at the protein level by IHC [25,56,[58][59][60], we observed the cellular expression pattern of MCT8 in the endothelial cells of vessels, and we demonstrate for the first time the expression of MCT8 in basal ganglia pericytes and the expression of MCT8 and OATP1C1 in monkey choroid plexus.…”
Section: Expression Pattern Of Th Transporters In the Human And Non-h...supporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with the previous findings at the protein level by IHC [25,56,[58][59][60], we observed the cellular expression pattern of MCT8 in the endothelial cells of vessels, and we demonstrate for the first time the expression of MCT8 in basal ganglia pericytes and the expression of MCT8 and OATP1C1 in monkey choroid plexus.…”
Section: Expression Pattern Of Th Transporters In the Human And Non-h...supporting
confidence: 92%
“…Additionally, some abundantly scattered fibers in the striatum showed MCT8 immunoreactivity in both humans and macaques. In the human brain sections, we have observed that there are aggregations of Corpora amylacea surrounding the lateral ventricles (Figure S2) which is consistent with our previous finding in the human cortex [25]. We also found some OATP1C1 immunoreactive depositions restricted to striatum gray matter neuropil and not present in white matter, in all seven human individuals under the antigen retrieval free condition (Figure S2).…”
Section: Mct8 and Oatp1c1 Are Expressed In Input Nuclei Of The Human ...supporting
confidence: 90%
See 3 more Smart Citations